Study of cement properties for plugging oil wells - M. Sh. Salamanova (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. Cementing oil and gas wells at a sufficiently large depth and at high temperatures is a rather complex and energy-intensive process that requires the use of special cement. The review material on oil well cements confirms the responsibility of choosing this binder, which can guarantee the safe process of drilling, plugging and operating oil wells. The classification of well cement is given, because it is known that when cementing free space in a well, specialists face various difficulties associated with temperature changes, density differences in the earth's crust.Method. The studies were carried out in accordance with the normative documents GOST 310.3-76 Cements. Methods for determining normal density, setting time and uniformity of volume change; GOST 1581- 2019 Oil-well portland cements. Specifications; GOST 310.4-81 Cements. Methods for determining the ultimate strength in bending and compression.Result. The properties of grouting cement PCT-I100 were studied, to slow down the setting of the mortar mixture for 10-14 hours, additives "Sulfatsel" and "NTF" retarders were introduced into the binder system with mixing water. The research results showed that the use of retardant additives slowed down the hardening of the system in the first 10 hours, but after setting, the cement stone quickly gained the missing strength. The water demand of oil well cement is quite high 33–35%, which is mandatory for obtaining a mobile mortar mixture, taking into account its injection by pumps into the space of an oil wellConclusion. The purpose of grouting cement confirms the responsibility and importance of selecting a binder for plugging wells and is determined by various factors, in particular, hydrogeological conditions, temperature, groundwater level in the layers of the earth's crust.